How Do Toxic Environments, Negative Gossip, And Islamic Workplace Spirituality Influence Knowledge Hiding? - Bakhri, Syaiful; Pariyanti, Eka (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2025)
AbstractThis study examines the impact of toxic workplace environments and negative workplace gossip on information concealing among lecturers. Furthermore, this research also investigates the influence of spirituality in the workplace from an Islamic standpoint as a moderating factor. This study centres on the academicians of private universities in Lampung, Indonesia. Data collection was conducted by delivering questionnaires to participants through both offline and online channels. The software application for data analysis is Jeffreys's Amazing Statistics Program (JASP). These results indicate a positive correlation between toxic workplace environments, unfavourable gossip, and knowledge hiding. Hence, it has been shown that workplace spirituality moderates the relationships inside toxic workplace environments. Negative workplace gossip correlates favourably with knowledge hiding. This study enhances the existing body of knowledge on social exchange theory by providing empirical evidence that validates the existence of social exchange in interpersonal interactions among academicians.